High-strength low-yield-ratio near-alpha type titanium alloy and preparation method thereof

By adding zirconium elements and euthanized β-stabilizing elements to the titanium alloy, a heterostructure is formed, and solid solution treatment and piercing deformation technology is adopted, the problem of high yield ratio of titanium alloy is solved, and high strength and low yield are achieved The combination of strong ratio and high elongation improves the processing and service performance of the material.

CN119464833AActive Publication Date: 2025-02-18INST OF METAL RESEARCH - CHINESE ACAD OF SCI +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411575014.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-18
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The yield strength of existing titanium alloys is relatively high, which leads to a reduction in molding capacity and a decrease in deformation resistance during cold processing, affecting the safety margin of the material.

Method used

By adding zirconium elements and euthanized β-stabilizing elements to the titanium alloy, a heterostructure with α′martensite combined with the primary α phase is formed, and solid solution treatment and piercing deformation are used to improve the strength and plastic deformation of the alloy. ability.

Benefits of technology

The coordination of high yield strength, low yield strength ratio and high elongation is achieved, and the work hardening capability and service safety of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464833A_ABST
    Figure CN119464833A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength low-yield-ratio near-alpha type titanium alloy and a preparation method thereof. The technical problem that in an existing titanium alloy, cooperation of high yield strength, high elongation and low yield ratio cannot be achieved is solved. The titanium alloy is composed of the following chemical components in percentage by weight: 10.0-15.0% of Zr, 10.0-15.0% of Ti, 10.0-15.0% of Ti and the balance of Ti. X: 0.5 to 10 percent; and the balance of Ti and inevitable impurities. Wherein x is one of eutectoid beta stable elements Fe, Mn, Cr, Ni or Cu, and the titanium alloy has the heterostructure texture characteristic that alpha'martensite is combined with a primary alpha phase; the preparation method of the titanium alloy comprises the following steps: providing raw materials according to the composition of the titanium alloy, carrying out smelting ingot casting on the raw materials, carrying out coping treatment, then carrying out homogenization treatment, cogging forging and two-phase region precision forging processing to form a blank, and then carrying out solid solution water quenching treatment; the method can be widely applied to the technical field of titanium alloy materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of titanium alloy materials, and in particular to a near-α-type titanium alloy with high strength and low yield ratio and a preparation method thereof. Background Art

[0002] At present, titanium alloys with light weight, high strength, excellent corrosion resistance and biocompatibility have been widely used in important fields such as aerospace, marine engineering, petrochemical industry, automobile industry and biomedicine. The yield strength ratio is an important mechanical index affecting the processing and engineering application of titanium alloys. However, the yield strength ratio (σ y / σ b ) is generally high, usually higher than 0.85, or even higher than 0.9, which is significantly higher than copper alloy (σ y / σ b =0.3~0.6)、aluminum alloy (σ y / σ b =0.5) and low and medium strength steel (σ y / σ b =0.6~0.8) and other traditional metal materials. A higher yield strength ratio not only reduces the forming ability of the material during cold working, but also reduces the deformation resistance of the material from yielding to plastic instability, which leads to a decrease in the safety margin of key titanium alloy structural parts during service. Therefore, the key mechanical parameter of yield strength ratio must be considered when developing a new generation of titanium alloys with excellent cold working forming performance and high safety margin.

[0003] At present, the technology in this field usually adopts alloy design to reduce the stability of β phase in titanium alloy, thereby utilizing stress-induced martensitic transformation or induced β twinning to reduce the yield ratio of titanium alloy. However, the above method is at the expense of the yield strength of titanium alloy, so that the yield strength of the alloy is usually less than 600MPa, which is obviously insufficient for key structural devices. The lower yield strength not only fails to meet the design requirements of the component under certain working conditions, but also significantly reduces the utilization rate of the material, which is very unfavorable for the lightweight of the component. Therefore, achieving the synergy of high yield strength, high elongation and low yield ratio in titanium alloy is still a problem to be solved. Summary of the invention

[0004] The purpose of the present invention is to solve the deficiencies of the above-mentioned technology and provide a near-α-type titanium alloy with high strength and low yield ratio and a preparation method thereof, so as to achieve the synergy of high yield strength, high elongation and low yield ratio.

[0005] To this end, the present invention provides a near-α-type titanium alloy with high strength and low yield ratio, wherein the chemical composition of the titanium alloy consists of the following components by weight percentage:

[0006] Zr: 10.0~15.0%;

[0007] x: 0.5-10%;

[0008] The balance is Ti and unavoidable impurities;

[0009] Wherein, x is one of the eutectoid β-stabilizing elements Fe, Mn, Cr, Ni or Cu, and the titanium alloy has a heterogeneous structure of α′ martensite combined with primary α phase.

[0010] Preferably, the size distribution of the heterogeneous structural phase of the titanium alloy is as follows: the size of the primary α phase is between 5 and 20 μm, and the size of the α′ martensite is between 0.5 and 1 μm.

[0011] Preferably, the titanium alloy has a yield strength of 900-1000 MPa, a yield strength ratio of no more than 0.80, and an elongation of no less than 11%.

[0012] A preparation method of a high-strength, low-yield ratio near-α-type titanium alloy, comprising the following steps: providing raw materials according to the composition of the high-strength, low-yield ratio near-α-type titanium alloy described in any one of the above items, fully smelting the raw materials to obtain ingots, grinding the ingots, homogenizing them, forging them, and processing them into billets in two-phase zone by solid solution quenching, and then obtaining titanium alloys.

[0013] Preferably, after the ingot is homogenized, it is subjected to blanking and drawing deformation. After solution treatment, it is kept warm in the single-phase region for a period of time and then subjected to drawing deformation with a total deformation of not less than 50%. Then, it is kept warm in the dual-phase region for a period of time and then subjected to drawing deformation with a total deformation of not more than 40%. Then, it is hot rolled and then subjected to solution quenching treatment to obtain a titanium alloy.

[0014] Preferably, the homogenization temperature of the ingot is 1100-1300°C.

[0015] Preferably, when heat preservation is carried out in the single-phase region, the heat preservation temperature is: the β phase transformation temperature T of the titanium alloy β +40℃, the holding time depends on the actual situation, usually 120min.

[0016] Preferably, when the dual phase region is kept warm, the holding temperature is: the β phase transformation temperature T of the titanium alloy β -40℃, the holding time depends on the actual situation, usually 120min.

[0017] Preferably, the hot rolling temperature is T β -40℃.

[0018] Preferably, rapid drawing deformation is performed in the single-phase region, with a deformation rate ranging from 40 to 50 mm / s; and slow drawing deformation is performed in the dual-phase region, with a deformation rate ranging from 5 to 10 mm / s.

[0019] Preferably, the solution temperature after blanking and drawing is T β -40℃.

[0020] Preferably, the solution temperature after hot rolling deformation is T β -40℃.

[0021] Preferably, the quenching medium is water.

[0022] Preferably, the raw material is smelted three times to obtain an ingot, and the raw material smelting device usually adopts a vacuum consumable furnace.

[0023] Preferably, the ingot is subjected to one drawing deformation after homogenization treatment at 1100-1300° C., three drawing deformations are performed after keeping the ingot in a single-phase region for a period of time, and three drawing deformations are performed after keeping the ingot in a dual-phase region for a period of time.

[0024] Preferably, the ingot after homogenization treatment at 1150°C is subjected to a blanking and drawing deformation, then subjected to a solid solution treatment, and then subjected to three drawing deformations in the single-phase region and three drawing deformations in the dual-phase region. β The plate of a certain thickness is prepared by hot rolling at -40℃, and finally the plate is subjected to solid solution quenching treatment to obtain an α-type titanium alloy plate having α′ martensite combined with primary α phase.

[0025] The design idea of ​​the present invention is:

[0026] The present invention adds zirconium and one of the appropriate eutectoid β-stabilizing elements Fe, Mn, Cr, Ni or Cu to the titanium alloy, so that the alloy forms a heterogeneous structure consisting of an α′ martensite phase and a primary α phase after solution treatment and water quenching, and at the same time improves the axial ratio of the α phase, thereby improving the alloy's strength while enhancing the alloy's work hardening ability and plastic deformation ability, thereby achieving a combination of high strength and low yield ratio.

[0027] The present invention provides a near-α-type titanium alloy with high strength and low yield ratio and a preparation method thereof, and the beneficial effects are:

[0028] (1) Different from the microstructure of existing titanium alloys for engineering, the titanium alloy provided by the present invention has a unique heterogeneous structure of α′ martensite combined with primary α phase, wherein the size of the primary α phase is between 5 and 20 μm, and the size of α′ martensite is between 0.5 and 1 μm.

[0029] (2) The method of the present invention can significantly reduce the yield strength ratio of the alloy while ensuring the yield strength and tensile strength of the alloy, thereby further increasing the service safety and reliability of the alloy while meeting the requirements for lightweight components.

[0030] (3) The method of the present invention can be used to prepare titanium alloy rods, wires, plates, etc., which can be widely used in many important fields such as aerospace, marine engineering, petrochemical industry, automobile industry and biomedicine.

[0031] (4) The method of the present invention can be used to obtain a series of dual-phase titanium alloys with different yield strengths and yield ratios, wherein the yield strength is not less than 900 MPa, the yield ratio is not higher than 0.80, and the elongation is not less than 11%, thereby meeting the different requirements of titanium alloys in cold forming and safe service. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application.

[0033] Figure 1 A typical engineering stress-strain curve diagram of the titanium alloy of the embodiment of the present application;

[0034] Figure 2 This is a scanning electron microscope photograph of the titanium alloy of the embodiment of the present application. DETAILED DESCRIPTION

[0035] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0036] The terms used in the following embodiments are only for the purpose of describing specific embodiments and are not intended to be limiting of the present application. As used in the specification and appended claims of the present application, the singular expressions "a", "an", "above", "the" and "this" are intended to also include expressions such as "one or more", unless there is a clear contrary indication in the context.

[0037] References to "one embodiment" or "some embodiments" etc. described in this specification mean that a particular feature, structure or characteristic described in conjunction with the embodiment is included in one or more embodiments of the present application. Thus, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. that appear at different places in this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways.

[0038] Unless otherwise specified, the methods used in the present invention are all conventional methods; the raw materials and devices used are all conventional commercially available products unless otherwise specified.

[0039] At present, the design of key titanium alloy structural devices in important fields such as aerospace, marine engineering, petrochemical industry, automobile industry and biomedicine, on the one hand, expects to have low yield strength and low yield ratio and excellent elongation during cold working to improve the cold deformation ability of the alloy, and on the other hand, expects titanium alloy to have high yield strength, high elongation and low yield ratio to ensure better service performance and safety margin of the alloy. However, the titanium alloy technology in this field sacrifices the yield strength of titanium alloy at the expense of stress-induced martensitic phase transformation or induced β twinning to reduce the yield ratio of titanium alloy, so that the yield strength of the alloy is less than 600MPa. Therefore, the current titanium alloy cannot meet the use requirements of key titanium alloy structural devices.

[0040] In order to solve the above technical problems, the present application provides a near-α-type titanium alloy with high strength and low yield ratio. The chemical composition of the titanium alloy consists of the following components by weight percentage:

[0041] Zr: 10.0~15.0%;

[0042] x: 0.5-10%;

[0043] The balance is Ti and unavoidable impurities; wherein x is one of the eutectoid β-stabilizing elements Fe, Mn, Cr, Ni or Cu, and the titanium alloy has a heterogeneous structure of α′ martensite combined with primary α phase.

[0044] In the titanium alloy, the content of Zr can be preferably 15.0% by weight. Zr is an α-phase neutral element in the titanium alloy, which plays a role in solid solution strengthening and increasing the strength of the alloy.

[0045] In the titanium alloy, the content of x can be preferably 5.0% by weight. The element x is one of Fe, Mn, Cr, Ni or Cu, and is a β-stabilizing element of the titanium alloy to strengthen the β-transformed structure, such as the role played by α′ martensite. In addition, the content of each x element in the titanium alloy is different, and its β-phase transformation temperature T β The metallographic method is usually used to determine the T in titanium alloys. β .

[0046] It should be noted that the titanium alloy in the embodiment of the present application, in addition to the above-mentioned Zr and x elements, also inevitably contains Ti and other inevitable impurities, wherein the inevitable impurities may include C, O and N, for example.

[0047] In one embodiment of the present application, the yield strength of the titanium alloy may be no less than 900 MPa, the yield strength ratio may be no more than 0.80, and the elongation may be no less than 11%.

[0048] Based on the above composition of the titanium alloy, the present application also provides a method for preparing a near-α-type titanium alloy with high strength and low yield ratio, and the preparation method may include the following steps:

[0049] S1. Provide raw materials according to the following composition of titanium alloy:

[0050] In terms of weight percentage, Zr is 10.0-15.0%, x is 0.5-10%; the balance is Ti; wherein x is selected from one of Fe, Mn, Cr, Ni or Cu;

[0051] The raw materials of the above-mentioned components can be selected from existing single metal raw materials or alloy raw materials, and can also be selected from existing recycled cutting materials or solid block materials.

[0052] S2. The raw materials are fully melted to obtain an ingot, and the ingot is ground to remove burrs.

[0053] In one embodiment of the present application, in the above step S2, the raw material is smelted at least three times to obtain an ingot. The smelting equipment may include an existing vacuum consumable furnace and other devices.

[0054] S3. homogenizing the ingot and forging the blank;

[0055] In one embodiment of the present application, after the ingot is homogenized, one or more blanking and drawing deformations are performed, and the number of blanking and drawing deformations is determined according to the actual situation. After the blanking and forging is completed, a solution treatment is preferably performed, and the solution temperature is preferably T β -40℃, so that the excess phase is fully dissolved. The homogenization temperature of the ingot is preferably 1100-1300℃, and the homogenization time is determined according to the actual situation. S4. Two-phase zone precision forging into billet. Among them:

[0056] In one embodiment of the present application, when heat preservation is performed in the single-phase region, the heat preservation temperature is preferably: the β phase transformation temperature T of the titanium alloy β +40℃, the holding time can be set to 120min according to the actual situation. Rapid pulling deformation is preferably carried out in the single-phase region, and the deformation rate range is 40-50mm / s. The number of pulling deformation is preferably at least three times, and the specific number is determined according to the actual situation. The total deformation amount of pulling deformation is preferably not less than 50%.

[0057] In one embodiment of the present application, when the dual phase region is kept warm, the holding temperature is: the β phase transformation temperature T of the titanium alloy β-40℃, the holding time can be set to 120min according to the actual situation. Slow pulling deformation is preferably carried out in the two-phase region, and the deformation rate range is 5-10mm / s. The number of pulling deformation is preferably at least three times, and the specific number is determined according to the actual situation. The total deformation amount of pulling deformation is preferably not less than 40%.

[0058] In one embodiment of the present application, the hot rolling temperature is preferably T β -40℃, and obtain slabs of suitable shape and size.

[0059] S5. Solution quenching treatment to obtain titanium alloy.

[0060] In one embodiment of the present application, the solution temperature after hot rolling deformation is preferably T β -40℃, the quenching medium is preferably water.

[0061] Figure 1 A typical engineering stress-strain curve diagram of a titanium alloy according to an embodiment of the present application is shown in FIG. Figure 1 As shown, after the material yields in the elastic deformation stage, it enters the plastic deformation stage and reaches the maximum stress, that is, the tensile strength is about 1300MPa. After that, the stress gradually decreases with the increase of strain. When the plastic strain reaches about 10%, the material breaks.

[0062] Figure 2 This is a scanning electron microscope photo of a titanium alloy of an embodiment of the present application, such as Figure 2 As shown, according to the contrast of the scanning electron microscope image, the alloy has two different phases, wherein the darker phase region corresponds to the primary α phase structure, and the brighter phase region with needle-like structure inside corresponds to the β transformation structure, i.e., the α′ martensite phase structure. It can be seen that the titanium alloy has a heterogeneous structure of α′ martensite combined with the primary α phase; wherein the size of the primary α phase is between 5 and 20 μm, and the size of the α′ martensite is between 0.5 and 1 μm.

[0063] The present application will be described and explained below through several groups of specific embodiments, but they should not be used to limit the scope of the present application.

[0064] Example 1

[0065] This embodiment is a near-α-type titanium alloy with high strength and low yield ratio. The chemical composition of the titanium alloy is specifically composed of the following components by weight percentage:

[0066] Zr: 10.0%;

[0067] x is Fe: 0.5%;

[0068] The balance is Ti and inevitable impurities.

[0069] The specific preparation method of the titanium alloy is as follows:

[0070] S1. Provide raw materials according to the following composition of titanium alloy:

[0071] In terms of weight percentage, Zr is 10.0%, Fe is 0.5% and the balance is Ti.

[0072] S2. A vacuum consumable furnace is used to perform three smelting processes to obtain a raw material ingot with uniform composition, and the ingot is ground.

[0073] S3. The ingot is homogenized at 1300℃ for 0.5h and then subjected to a blanking and drawing deformation. After the blanking and forging is completed, a solid solution treatment is performed at a solid solution temperature of 740℃.

[0074] S4. Two-phase zone precision forging into billet. Wherein:

[0075] When the single-phase region is kept warm, the temperature is 820°C and the time is 120 minutes. Three rapid pull-out deformations are carried out in the single-phase region, the deformation rate ranges from 40 to 50 mm / s, and the total deformation of the pull-out deformation is not less than 50%.

[0076] When the heat preservation is carried out in the dual phase region, the heat preservation temperature is 740℃ and the heat preservation time is 120min. Three slow pull-out deformations are carried out in the dual phase region, the deformation rate ranges from 5 to 10mm / s, and the total deformation of the pull-out deformation is not less than 40%.

[0077] Hot rolling is performed at 740°C to obtain a slab with a thickness of 30 mm. It should be noted that in the actual production process, the thickness of the slab can be determined according to the actual situation to ensure hardenability.

[0078] S5. Solution quenching treatment, wherein the solution temperature is 740°C, the holding time is 0.5h, and then water quenching is performed to obtain a near-α-type titanium alloy plate with high strength and low yield strength ratio.

[0079] Example 2

[0080] Example 2 is a near-α-type titanium alloy with high strength and low yield ratio, which is different from Example 1 in that:

[0081] (1) The composition of titanium alloys is different. The composition of specific titanium alloys is listed in Table 1.

[0082] (2) The solution temperature in step S3 is 770°C; in step S4, the single-phase region insulation temperature is 850°C, the dual-phase region insulation temperature is 770°C, and the hot rolling temperature is 770°C; the solution temperature in step S5 is 770°C.

[0083] The other contents are the same as those of Example 1 and will not be repeated here.

[0084] Example 3

[0085] Example 3 is a near-α-type titanium alloy with high strength and low yield ratio, which is different from Example 1 in that:

[0086] (1) The composition of titanium alloys is different. The composition of specific titanium alloys is listed in Table 1.

[0087] (2) In step S3, the homogenization temperature of the ingot is 1250°C and the solution temperature is 770°C; in step S4, the single-phase region insulation temperature is 850°C, the dual-phase region insulation temperature is 770°C, and the hot rolling temperature is 770°C; in step S5, the solution temperature is 770°C.

[0088] The other contents are the same as those of Example 1 and will not be repeated here.

[0089] Example 4

[0090] Example 4 is a near-α-type titanium alloy with high strength and low yield ratio, which is different from Example 1 in that:

[0091] (1) The composition of titanium alloys is different. The composition of specific titanium alloys is listed in Table 1.

[0092] (2) In step S3, the homogenization treatment temperature of the ingot is 1200°C and the solid solution temperature is 750°C; in step S4, the single-phase region insulation temperature is 830°C, the dual-phase region insulation temperature is 750°C, and the hot rolling temperature is 750°C; in step S5, the solid solution temperature is 750°C.

[0093] The other contents are the same as those of Example 1 and will not be repeated here.

[0094] Example 5

[0095] Example 5 is a near-α-type titanium alloy with high strength and low yield ratio, which is different from Example 1 in that:

[0096] (1) The composition of titanium alloys is different. The composition of specific titanium alloys is listed in Table 1.

[0097] (2) In step S3, the homogenization temperature of the ingot is 1150°C and the solution temperature is 730°C; in step S4, the single-phase region insulation temperature is 810°C, the dual-phase region insulation temperature is 730°C, and the hot rolling temperature is 730°C; in step S5, the solution temperature is 730°C.

[0098] The other contents are the same as those of Example 1 and will not be repeated here.

[0099] Example 6

[0100] Example 6 is a near-α-type titanium alloy with high strength and low yield ratio, which is different from Example 1 in that:

[0101] (1) The composition of titanium alloys is different. The composition of specific titanium alloys is listed in Table 1.

[0102] (2) In step S3, the homogenization temperature of the ingot is 1100°C and the solution temperature is 700°C; in step S4, the single-phase region insulation temperature is 780°C, the dual-phase region insulation temperature is 700°C, and the hot rolling temperature is 700°C; in step S5, the solution temperature is 700°C.

[0103] The other contents are the same as those of Example 1 and will not be repeated here.

[0104] Table 1 Raw material composition of titanium alloys in Examples 1 to 6

[0105]

[0106] Tensile properties test

[0107] According to GB / T 228.1-2021, the room temperature tensile mechanical properties of the titanium alloy plates (i.e., test specimens) prepared in Examples 1 to 6 were tested using a Zwick Z150 tensile testing machine at a tensile rate of 0.3 mm / min. Three parallel samples were taken from each group of test specimens, and the test results were averaged. The mechanical properties obtained from the experiment included yield strength, tensile strength, and elongation. The results are shown in Table 2.

[0108] Table 2 Mechanical properties test results of titanium alloy products of Examples 1 to 6

[0109]

[0110]

[0111] It can be seen from the test data of Examples 1 to 6 in Table 2 that the yield strength of the titanium alloy of the present invention is 900 to 1000 MPa, the tensile strength is not less than 1200 MPa, the yield strength ratio is not higher than 0.80, and the elongation is not less than 11%.

[0112] It can be seen that while improving the strength of titanium alloy, the alloy's work hardening ability and plastic deformation ability are improved, thereby obtaining a combination of high strength and low yield ratio, achieving the synergy of high yield strength, high elongation and low yield ratio, and obtaining a near-α titanium alloy with both high strength and low yield ratio and an α′ martensite combined with a primary α phase heterogeneous structure. It can be widely used in important fields such as aerospace, marine engineering, petrochemical industry, automotive industry, and biomedicine.

[0113] It should be noted that, in addition to preparing titanium alloy plates, the method of the present invention can also prepare titanium alloy bars, wires and other products.

[0114] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A near-α-type titanium alloy with high strength and low yield ratio, characterized in that: The chemical composition of the titanium alloy consists of the following components by weight percentage: Zr:10.0~15.0%; x:0.5~10%; The balance is Ti and unavoidable impurities; Wherein, the x is one of the eutectoid β-stabilizing elements Fe, Mn, Cr, Ni or Cu, and the titanium alloy has a heterogeneous structure of α′ martensite combined with primary α phase.

2. A near-α-type titanium alloy with high strength and low yield ratio according to claim 1, characterized in that: The size distribution of the heterogeneous structural phase of the titanium alloy is as follows: the size of the primary α phase is between 5 and 20 μm, and the size of the α′ martensite is between 0.5 and 1 μm.

3. A near-α-type titanium alloy with high strength and low yield ratio according to claim 1 or 2, characterized in that: The yield strength of the titanium alloy is 900-1000 MPa, the yield strength ratio is not higher than 0.80, and the elongation is not lower than 11%.

4. A method for preparing a near-α-type titanium alloy with high strength and low yield ratio as claimed in claim 1, characterized in that the steps include: A raw material is provided according to the composition of the high-strength, low-yield ratio near-α-type titanium alloy as described in any one of claims 1 to 3, the raw material is fully smelted to obtain an ingot, the ingot is subjected to a grinding treatment, homogenization treatment, open forging, two-phase zone precision forging to form a billet, and then solution quenching treatment to obtain the titanium alloy.

5. The method for preparing the near-α-type titanium alloy with high strength and low yield ratio according to claim 4, characterized in that: After the ingot is homogenized, it is subjected to blanking and drawing deformation. After solution treatment, it is kept in a single-phase region for a period of time and then subjected to drawing deformation with a total deformation of not less than 50%. After keeping in a two-phase region for a period of time, it is subjected to drawing deformation with a total deformation of not more than 40%. Then, it is hot rolled and subjected to solution quenching treatment to obtain the titanium alloy.

6. The high-strength, low-yield ratio near-α-type titanium alloy and the preparation method thereof according to claim 4, characterized in that: The homogenization treatment temperature of the ingot is 1100-1300°C.

7. The high-strength, low-yield ratio near-α-type titanium alloy and the preparation method thereof according to claim 5, characterized in that: When heat preservation is carried out in the single-phase region, the heat preservation temperature is T β +40℃; when keeping warm in the two-phase region, the keeping temperature is T β -40℃; hot rolling temperature is T β -40℃.

8. The high-strength, low-yield ratio near-α-type titanium alloy and the preparation method thereof according to claim 5, characterized in that: In the single-phase region, rapid pull-out deformation is carried out with a deformation rate ranging from 40 to 50 mm / s; in the dual-phase region, slow pull-out deformation is carried out with a deformation rate ranging from 5 to 10 mm / s.

9. The near-α-type titanium alloy with high strength and low yield ratio and the preparation method thereof according to claim 5, characterized in that: The solution temperature after billet opening and drawing is T β -40℃, the solution temperature after hot rolling deformation is T β -40℃, quenching medium is water.

10. The near-α-type titanium alloy with high strength and low yield ratio and the preparation method thereof according to claim 4, characterized in that: The raw material is smelted three times to obtain an ingot, the ingot is homogenized at 1100-1300°C and then subjected to a blanking and drawing deformation, then subjected to a third drawing deformation after being kept in a single-phase region for a period of time, and then subjected to a third drawing deformation after being kept in a dual-phase region for a period of time.

Citation Information

Patent Citations

  • High-strength titanium alloy and preparation method thereof

    CN108913948A

  • Corrosion-resistant titanium alloy and preparation method thereof

    CN109097623A

  • Equiaxed nanocrystalline Ti-Zr-Cr alloy with high thermal stability and preparation method thereof

    CN112063891A

  • Equiaxed nanocrystalline Ti-Zr-Mn alloy with high thermal stability and preparation method thereof

    CN112063892A

  • High-thermal-stability equiaxed nanocrystal Ti-Zr-Fe alloy and production method thereof

    CN112195365A